The Discovery of the Theater of Akragas (Valley of Temples, Agrigento, Italy): An Archaeological Confirmation of the Supposed Buried Structures from a Geophysical Survey - Marilena Cozzolino; Luigi Maria Caliò; Vincenzo Gentile; Paolo Mauriello; Andrea Di Meo (Geosciences, 2020)
The theater of the ancient city of Akragas has been researched for centuries and, in 2016, a multidisciplinary and multi-scale research work that involved topographic studies, analysis of satellite images, geomorphological characterization of the land, archaeological surveys, and non-invasive geophysical surveys led to its discovery. In this work, a comparison between the archaeological structures hypothesized by geophysical results and the archaeological structure excavated is presented. The area of about 5.500 m2 was investigated using electrical resistivity tomography (ERT). The survey highlighted a series of resistivity highs arranged on concentric semicircles defining perfectly the presence of an articulate building attributable to a theatrical complex of imposing dimensions (diameter of about 95 m). Archaeological excavation led to the identification of the summa cavea with the discovery of foundation-level structures arranged on a semicircle, on which the tiers were located, and cuts in the rock with seat imprints. The overlap of the technical layouts obtained from the documentation of archaeological excavation on the modelled resistivity maps shows the perfect correspondence between the features of the resistivity highs and the ancient structures actually found.